2006
DOI: 10.1002/nme.1613
|View full text |Cite
|
Sign up to set email alerts
|

Galerkin boundary integral analysis for the axisymmetric Laplace equation

Abstract: SUMMARYThe boundary integral equation for the axisymmetric Laplace equation is solved by employing modified Galerkin weight functions. The alternative weights smooth out the singularity of the Green's function at the symmetry axis, and restore symmetry to the formulation. As a consequence, special treatment of the axis equations is avoided, and a symmetric-Galerkin formulation would be possible. For the singular integration, the integrals containing a logarithmic singularity are converted to a non-singular for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…The integral formulation of equation (2) is solved using a BEM with an axisymmetric Galerkin approximation of the BI [5], with linear and quadratic shape functions [4], and an interface velocity obtained by postprocessing the BI solution ∂φ ∂n on the interface using a Galerkin technique. For equations (3) and (4), first or second order upwind finite differences in space and first order in time are used.…”
Section: Numerical Approximation and Resultsmentioning
confidence: 99%
“…The integral formulation of equation (2) is solved using a BEM with an axisymmetric Galerkin approximation of the BI [5], with linear and quadratic shape functions [4], and an interface velocity obtained by postprocessing the BI solution ∂φ ∂n on the interface using a Galerkin technique. For equations (3) and (4), first or second order upwind finite differences in space and first order in time are used.…”
Section: Numerical Approximation and Resultsmentioning
confidence: 99%
“…The free surface equations (7) and (8) have now been embedded into the higher dimension equations (15) and (16) and it can be shown that system (13)- (16) is equivalent to system (5)- (8). In fact, this enriches the kinematics of the system, in the sense that it can incorporate topological changes of the free surface, and as well the evolution of the associated potential function within this boundary; see [8,14].…”
Section: Level Set Embeddingmentioning
confidence: 99%
“…It is also worth noting that there are other significant differences with the boundary integral approximations employed in [6,7]. Herein, a linear element Galerkin method [16] is employed, in contrast to the high-order collocation approximation in [6,7], and the methods for computing the critical surface gradient are completely different. With the linear element discretization and N p free boundary nodes, the boundary integral equations for the exterior and interior fluids, Eqs.…”
Section: Boundary Integral Equationsmentioning
confidence: 99%
See 2 more Smart Citations